Konsep Kesejahteraan Perspektif Ashabiyah Ibnu Khaldun Dalam Wisata Religi Tebuireng - Arfaq, Fadlulloh Fakhrudin; Hendratmi, Achsania; Ramadhan, Dwi Swasana (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2020)
The concept of welfare has developed significantly, but its implementation has not been optimal. One of the concepts of welfare proposed by Ibn Khaldun about circle of equity and the concept of ashabiyah can be a reference. This article aims to analyze the concept of the welfare of Ibn Khaldun's Ashabiyah perspective by taking samples of community research around Tebuireng religious tourism. This research article uses a qualitative approach to the type of case study research. Data collection techniques using direct interviews, documentation and observation. The results of the analysis show that religious tourism in Tebuireng is beneficial to the communities around and within the religious tourism area and the focus of management on religious tourism is the community with synergies between community groups that need to be improved.